Análisis de costos en la producción láctea de las mipymes del sector Joseguango alto, del cantón Latacunga, en el periodo económico 2017. - Gualdrón Arias, Eliana Xiomara (2018)
Now the milk MiPymes have now become an important productive sector for the region and the country, contributing to Producto Interno Bruto (PIB) a considerable percentage of approximately 8%, it is also important to indicate that have become generators of direct jobs and Indirect jobs. The research understand the analysis the costs involved in the milk production in the MiPymes in the Joseguango Alto sector, in the Latacunga canton, in 2017 economic period. In the process of the research the quantitative methodology was applied because the facts were quantified, the interpretation and analysis of the results obtained were carried out, as well as the documentary research was used, through national and international authors which allowed to base the theoretical framework and as a fundamental method the inductive was used, that showal us to start from the basics of the processes in order to conclude the research. As a research technique, the survey was used, which allowed an approach to the population and facilitated the collection of information. The field work was carried out where it was possible to verify directly the event of the facts and the obtaining of necessary information, being able to reach alternatives of proposal, and through descriptive research it was possible to accept the characteristics of the different processes carried out not only individually, but also in a group way, and it was thus possible to reach a problem approach. The main results determined that milk MiPymes have remained static over time, since despite the continuous work have not achieved the expected results, losing spaces within the market that everyday is more demanding and competitive, because enterprise do not have the correct management of the elements of the cost, they lack the techniques and mechanisms for the correct analysis of the information, creating barriers for the continuous improvement, causing of this form incidence in the decision making and an impact Social high.